INTERNALISASI PENDIDIKAN AQIDAH DALAM KITAB AL-MUQTATHOFAT LI AHLI Al-BIDAYAT KARYA KH. MARZUKI MUSTAMAR - Lisaudaturohmah Lisaudaturohmah; Abdul Jalil; Devi Wahyu Ertanti (VICRATINA, 2019)
The public who learn religion by self-learning through the Internet, some high school that there are material that has been smelly radical and intolerant in PAI subjects. 1) The educational concept of aqidah Islam, 2) The concept of education aqidah in al-muqtathofat li ahli al-bidayat, 3) Form the implementation of education internalization aqidah. research is done with a qualitative approach, the type of case study research. data collection techniques with observation methods, in-depth interviewsnand documentation. Data analysis techniques by Miles and Hubarman with data reduction, display data, conclusion drawing/verivication. Check the validity of data with an extension of observation, improve persistence, triangulation, and peer checking. 1) educational concept of aqidah in madrasah diniyah SMA Islam Sabilurrosyad reflected in the vision of the mission. 2) educational concept of aqidah in madrasah diniyah SMA Islam Sabilurrosyad There are 5 kinds of lisanul hal, ittibaul ulama, bertaqlid/ bermadzhab, Islam and indonesia, and tawasuth, tawazun, tasamuh. 3) Form of education of aqidah in madrasah diniyah SMA Islam sabilurrosyad is reading nadham and letters of choice, istighosah, maulid diba, sholawat burdah, manaqib, khataman al-quran, tahlilan and send prayers, prayer of bodies and prayers ghoib, celebration of islamic day, and the discussion of plainness.